Effect of the isotiazole adjuvants in combination with cisplatin in chemotherapy of neuroepithelial tumors: experimental results and modeling - Vladimir Potkin; Aliaxandr Pushkarchuk; Alexandra Zamaro; Hongwei Zhou; Sergey Kilin; Sergey Petkevich; Irina Kolesnik; Dominik L. Michels; Dmitry A. Lyakhov; Vladimir A. Kulchitsky (Scientific Reports, 2023)
Abstract Chemotherapy is one of the main treatment options for cancer, but it is usually accompanied with negative side effects. The classical drugs combination with synergistic adjuvants can be the solution to this problem, allowing reducing therapeutic dose. Elucidating the mechanism of adjuvant action is of key importance for the selection of the optimal agent. Here we examine the system drug-adjuvant to explain the observed effect in practice. We used the first line drug cisplatin. Morpholinium and 4-methylpiperazinium 4,5-dichloro isothiazol-3-carboxylates were selected as adjuvants. The study of the cisplatin-adjuvant system was carried out by quantum chemical modeling using DFT. It turned out that adjuvants form conjugates with cisplatin that lead to the relocation of frontier molecular orbitals as well as increase of conjugate’s dipole moment. It resulted in change of the interaction character with DNA and increase of the bioactivity of the system. The data obtained are the basis for expanding the studies to include other drugs and adjuvants. Oncologists will have opportunity to use “classical” chemotherapy drugs in combination with synergists for those patients who have not been previously recommended to such a treatment because of pronounced toxic side effects.